Indigenous People - Venkatesan, Purushothaman (IntechOpen, 2017)
Indigenous peoples are the native ethnic groups, who are descended from and identified with the original inhabitants of a region, in contrast to groups that have settled, occupied, or colonized the area more recently. This book entitled Indigenous People is an attempt to bring out the analysis of indigenous environment, indigenous technical knowledge, indigenous resource governance, and indigenous entrepreneurship and empowerment. This book contains selected chapters from renowned personalities from across the globe who have rich knowledge on sovereignty, economic well-being, and resource access of the indigenous people, on which their cultures depend. This book will certainly be an asset or a boon, not only to the extension fraternity but also to all those who are really thirsty of information and knowledge on indigenous people.